Por uma psicologia não-fascista para um mundo catastrófico: a experiência de profissionais de psicologia face a lgbtfobia. - Carvalho, Bruno Robson de Barros (2020)
This thesis, as a situated production, has the tone of its time and context in which was produced, crossed by subjective (dis)encounters with health psychology professionals with experience in assisting people in situations of LGBTphobia in a global political crisis with dense national modulations. Interviews were conducted with eight psychology professionals and other discursive Productions (between 473 photos, 199 audios and 5 diaries) from which, directly or indirectly, the lines of argument and analysis of this research were sewn, between knowledge, power games and intersubjectivities. Considering the research also as production of oneself, in the researcher's experience stories erupt about facts, fictions and affections. Thus, the narratives produced, through interviews and diaries, tell not only about the research process on the psychological practice response to LGBTphobia, but also a self-writing committed ethically, aesthetically and politically to the complexity of the present. As a result of this meeting between researcher and professionals, a thesis, na event, figuratively understood as a revolution, a catastrophe! Stories about the genocide of traditional people, the brutalization of black bodies, the climate collapse, the impeachment of Dilma Rousseff, the presidential elections and the beginning of the Bolsonaro government are counted not only to evoke a problematization about the psychological practice of victims of LGBTphobia, but also produce a version for registration and inscription of the present history. Professionals and researcher amalgamate experiences and as a result, the confrontation with the end of the world, with Humans and its Humanity. O Anthropocene, the limit event of catastrophe and destitution, puts Psychology to the test, regarding to its love of power, technique and fascism. As a destination, in attempt to differ, psychology professionals are invited to happen, to rise up taking distance from power as an instrument of domination. Making a non-fascist psychology, the meaning to an ethical care of the self clinic and freedom practices aimed at destitute people, who had its urgencies kidnapped in a country made up from bloodshed and apology for fear and hatred.